2008
DOI: 10.1007/s10823-008-9063-9
|View full text |Cite
|
Sign up to set email alerts
|

Health and Health Perceptions Among Kenyan Grandparents

Abstract: The dramatic increase in the aging population in developed countries has led to an explosion of research on health and aging in the United States. Few studies, however, have been conducted in developing countries, even though many of these populations are experiencing a faster rate of growth in the 65+ population. Thus, although our knowledge of health and aging has increased, our knowledge of the variation in health as people age is limited. While the numbers of older adults is increasing in Africa, very litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 36 publications
0
21
0
2
Order By: Relevance
“…It was hypothesized at that time that food alloca tion was biased toward men and that women had higher energy expenditure due to increased caregiving activities, resulting in a negative energy balance among grandmothers. A larger study conducted in 2005 found little impact of caregiving on health or nutrition and the reverse effect of gender on nutri tion (Ice, Zidron, and Juma 2008). The purpose of this article is to examine the impact of caregiving on health using longitudinal data.…”
Section: Caregiving and Healthmentioning
confidence: 99%
“…It was hypothesized at that time that food alloca tion was biased toward men and that women had higher energy expenditure due to increased caregiving activities, resulting in a negative energy balance among grandmothers. A larger study conducted in 2005 found little impact of caregiving on health or nutrition and the reverse effect of gender on nutri tion (Ice, Zidron, and Juma 2008). The purpose of this article is to examine the impact of caregiving on health using longitudinal data.…”
Section: Caregiving and Healthmentioning
confidence: 99%
“…The physical needs depending on the stage of the patient include bathing, searching for food, cooking, and feeding the sick, dressing, lifting the sick to the toilet, fetching water, and gardening; whereas nursing care includes pain management, treating wounds, administering medications, and walking long distances to health facilities (Akintola 2006, UNAIDS 1997. However, a study by Ice et al (2008) on a small sample of Luo grandparents found no difference on the health of elderly caregivers of AIDS orphans and PLWHA compared with non-caregivers. The use of a small sample and only in one community limited the generalizations of the findings, hence the need for more studies in different communities and with larger samples.…”
Section: Affected By Hiv/aidsmentioning
confidence: 88%
“…Research on older people in Africa is scarce and the few studies done cover only a few countries without taking into consideration the wide diversity of communities on the continent of Africa or use smaller samples which make it difficult to generalize findings (Bock and Johnson 2008, Ice et al 2008, Makoni 2008, Kiggundu and Oldewage-Theron 2009, Kyobutungi et al 2009, Lombard and Kruger 2009, Muga and Onyango-Ouma 2009). …”
Section: International Journal Of Health Promotion and Education 251mentioning
confidence: 99%
See 2 more Smart Citations